Neoflavonoid dalbergiphenol from heartwood of Dalbergia sissoo acts as bone savior in an estrogen withdrawal model for osteoporosis. Issue 11 (November 2015) - Gautam, Jyoti; Kumar, Padam; Kushwaha, Priyanka; Khedgikar, Vikram; Choudhary, Dharmendra; Singh, Divya; Maurya, Rakesh; Trivedi, Ritu
Abstract: Objective: Dalbergiphenol (DGP) is a neoflavonoid isolated from heartwood of Dalbergia sissoo . Effects of DGP on skeletal health remain to be elucidated. The objective of the present study was to investigate the biological effects of DGP on bone loss in ovariectomized mice. Methods: Adult BALB/c mice were ovariectomized and administered DGP (1 and 5 mg/kg/d) or 17β-estradiol (E2 ) orally for 6 weeks. The sham group and the ovariectomy (OVX) + vehicle group served as controls. Eight female BALB/c mice were taken for each group. Uterine estrogenicity, bone microarchitecture, biomechanical strength, new bone formation (based on bone formation rate and mineral apposition rate), and skeletal expression of osteogenic and resorptive gene markers were studied. Results: OVX resulted in a marked increase in body weight and a decrease in femoral and vertebral trabecular bone volume that were prevented by DGP or E2 treatment. DGP treatment increased bone biomechanical strength and new bone formation rate in ovariectomized mice, comparable with E2 treatment. However, increase in uterine weight and estrogenicity were observed in E2 -treated ovariectomized mice, but not in response to DGP treatment. Treatment with DGP increased messenger RNA expression of runt-related transcription factor 2, osterix, and collagen type I, and decreased messenger RNA expression of tartrate-resistant acid phosphatase and the osteoprotegerin–to–receptor activator of nuclear factor-κB ligand ratio in the femur of ovariectomized mice. Conclusions: Overall findings suggest that DGP treatment can effectively prevent OVX-induced increase in bone loss and decrease in bone strength possibly by increasing osteoblastic activities and by decreasing osteoclastic activities.